2011
DOI: 10.1592/phco.31.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the 4Ts Pretest Clinical Scoring System as a Predictor of Heparin‐Induced Thrombocytopenia

Abstract: A low 4Ts score supports a low probability of HIT based on the results of the polyspecific ELISA. Overall, the interrater reliability of the scoring system was fair. Components of the 4Ts scoring system need to be further clarified or modified in order to improve interrater reliability and thereby increase the clinical utility of this pretest probability model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…10,37,38 Inter-rater agreement was assessed in only one eligible study 10 and therefore could not be addressed in our meta-analysis, but is an important potential shortcoming of the 4Ts that merits further investigation. Newer scoring models, including a revised version of the 4Ts, include more detailed and explicit itemization of clinical features in an attempt to clarify their meaning and enhance reproducibility among raters.…”
Section: Discussionmentioning
confidence: 99%
“…10,37,38 Inter-rater agreement was assessed in only one eligible study 10 and therefore could not be addressed in our meta-analysis, but is an important potential shortcoming of the 4Ts that merits further investigation. Newer scoring models, including a revised version of the 4Ts, include more detailed and explicit itemization of clinical features in an attempt to clarify their meaning and enhance reproducibility among raters.…”
Section: Discussionmentioning
confidence: 99%
“…Strutt et al [11] reported eight of 13 intermediate scoring patients and one of five high scoring patients with a positive PaGIA were not commenced on alternative anticoagulation. Although it appears that this may represent suboptimal management, we feel that it is likely to reflect a widely experienced difficulty in managing the often very complicated clinical scenario of potential HIT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the diagnosis of HIT is difficult in critically ill patients as both leading symptoms of HIT (thrombocytopenia and thrombosis) are not specific [21] . Although the absence of antiheparin/PF antibodies has a high negative predictive value to exclude HIT, it is not sufficient to detect these antibodies without further satisfying the stepwise criteria (Figure 1) including the 4Ts pretest clinical score [13,14] for the diagnosis of HIT [7,[9][10][11]15] . Our literature research revealed six studies, nine case reports, and six case series on anti-PF4/ heparin antibodies or HIT in solid organ transplant candidates and recipients.…”
Section: Assfalg V Et Al Hit In Solid Organ Transplant Recipientsmentioning
confidence: 99%
“…Overall, none of the liver transplant recipients developed HITTS in their systematic study. Furthermore, recipients who were clinically suspected to suffer from HIT according to 4Ts pretest clinical scoring system [7,[12][13][14] did not develop platelet activating antibodies in HIPA [61] .…”
Section: Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation